Multilingualism as a Resource and a Goal Using and Learning Languages in Mainstream Schools - Turner, Marianne (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This timely volume is an important contribution to the fast expanding literature on Translanguaging. The coverage of mainstream school education, TESOL, CLIL and EMI is most impressive. The rich data from the Australian context have significant implications for school management, pedagogy and the learning outcomes of bi/multilinguals worldwide." --Li Wei, Chair of Applied Linguistics, University College London, UK This book explores multilingualism as a resource and goal at school in contexts of student diversity and institutional monolingualism. Combining translanguaging theory and sociocultural theory, the author proposes a framework for the learning and use of both foreign and heritage languages across the curriculum in mainstream schools. By clearly linking language practices to teaching and learning objectives, the book aims to support school leaders and practitioners make informed decisions about how best to promote multilingualism in their school, as wellas to enhance the learning outcomes of bi/multilinguals. In addition to school leaders and practitioners, it will be of interest to students and academics in the fields of bilingual education and TESOL, as well as applied linguistics and language teaching more broadly. Marianne Turner is Senior Lecturer in Bilingual Education and TESOL at Monash University, Australia. She researches context-sensitive approaches to the integration of language and content in English as an Additional Language (EAL), foreign and heritage language settings.